Spatial variation of trace element concentration and contamination assessment in the coral reef sediments of Lakshadweep Archipelago, Indian Ocean. (September 2019) - Joy, Anu; P P, Anoop; R, Rajesh; Mathew, Jose; Mathew, Angel; Gopinath, Anu
Abstract: Surface sediments were collected from the shore and lagoons of Kavaratti, Kadmat and Agatti islands of Lakshadweep Archipelago and analysed for trace element concentration. The sediment contamination was assessed on the basis of geochemical, biological hazard and ecological risk indices. Except Cd and Pb, all the other trace elements selected for the study were below the contamination level. Compared to Kadmat, Kavaratti and Agatti were more polluted and the pollution was pronounced in lagoons than shore. Population pressure, untreated sewage, diesel based power generation, shipping and tourism activities contribute to sediment contamination. Statistical analysis revealed the association of trace elements with sedimentary characteristics due to anthropogenic sources. Highlights: Coral reef sediments of Lakshadweep Archipelago are polluted by cadmium and lead. Serious contamination was observed in Agatti and Kavaratti based on geochemical and ecological risk assessment indices. Kadmat was the least polluted due to less population pressure and anthropogenic activities. Diesel based power generation, shipping activities and dumping of untreated sewage are the main sources of Cd and Pb.